ANTIOXIDANT ACTIVITIES OF ROPINIROLE AND PRAMIPEXOLE NOVEL DRUGS USED IN TREATMENT OF PARKINSONISM: AN IN VITRO APPROACH - Selva, Preetha; Vengadassalapathy, Srinivasan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of this study is to evaluate and compare the free radical scavenging activities of selective dopamine agonist namely ropinirole and pramipexole. Methods: The antioxidant activity of ropinirole and pramipexole at various concentrations was done by 1, 1-diphenyl-2picrylhydrazyl (DPPH) free radical scavenging assay comparing it with ascorbic acid which was taken as standard. Results: The free radical scavenging property as measured by DPPH method showed that ropinirole and pramipexole have got a potent free radical scavenging activity with that of ascorbic acid. Conclusion: Novel drugs such as pramipexole and ropinirole are promising molecules in the field of oxidative damage related neurodegenerative disorders providing us an optimistic targeted approach toward neuroprotection. Keywords: Free radical scavenging, 1, 1-diphenyl-2picrylhydrazyl assay, Anti-Parkinson's, Dopamine agonist.